(untitled) (Academia Science Repository, 2023)
In this article, we consider the features of teaching a foreign language in vocational education in the context of a forced transition to distance learning. The article pays special attention to the comparison of methods of teaching a foreign language in traditional approach and online classes. The author highlights both positive and negative aspects of teaching a foreign language in vocational education in the context of a forced transition to distance learning, but comes to the conclusion that, given the specifics of teaching a foreign language, blended learning (Blended learning). The author emphasizes that the specificity of teaching a foreign language in vocational education requires direct contact between the teacher and the student in order to creating a language environment for communication in the classroom, which does not exclude the use of digital technologies.